Higher-order transformations for the generation of synchronization infrastructures in blended modeling - Latifaj, Malvina; Ciccozzi, Federico; Mohlin, Mattias (Frontiers in Computer Science, 2023)
Blended modeling aims at boosting the development of complex multi-domain systems by enabling seamless multi-notation modeling. The synchronization mechanisms between notations are embodied in model transformations. Manually defining model transformations requires specific knowledge of transformation languages, and it is a time-consuming and error-prone task. Moreover, whenever any of the synchronized languages or notations evolves, those transformations become obsolete. In this paper, we propose an automated solution for generating synchronization transformations in an industrial setting. Although our main goal was to provide a solution for synchronization between graphical and textual notations of UML-RT state machines, the proposed approach is language- and notation-agnostic. The approach entails i) the specification of mapping rules between two arbitrary domain-specific modeling languages leveraging a mapping modeling language, appositely defined for this purpose, and ii) the automatic generation of synchronization model transformations driven by the mapping rules. We validated the proposed approach in two use cases.